2019
DOI: 10.1200/jgo.17.00241
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prognostic Factors and Outcome in Pediatric Osteosarcoma: Effect of Delay in Local Control and Degree of Necrosis in a Multidisciplinary Setting in Lebanon

Abstract: PURPOSE Outcomes in pediatric osteosarcoma have dramatically improved over the past few decades, with overall survival rates of 70% and 30% for patients with localized and metastatic disease, respectively. PATIENTS AND METHODS We retrospectively reviewed clinical characteristics and outcomes of 38 patients treated between 2001 and 2012 at a single institution in Lebanon. All patients received a uniform three-drug chemotherapy regimen consisting of cisplatin, doxorubicin, and methotrexate. Ifosfamide and etopos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
10
0
2
Order By: Relevance
“…In addition, it is one of the few studies describing patient and treatment characteristics in three different age groups and therefore it could be directive to future studies. Other studies describe small study populations or present data from prospective or randomized controlled trials with different pre-empted endpoints and inclusion criteria [8,9,[14][15][16][17][18].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it is one of the few studies describing patient and treatment characteristics in three different age groups and therefore it could be directive to future studies. Other studies describe small study populations or present data from prospective or randomized controlled trials with different pre-empted endpoints and inclusion criteria [8,9,[14][15][16][17][18].…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In contrast, some studies stated that no differences in survival were found between pediatric patients and older adults [11,12]. The variation in survival probabilities among age groups might be due to differences in tumor characteristics, chemotherapy regimens, pathohistological response, or different patient characteristics [9,[13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…Longer duration of hospitalization reflects the burden of therapy-induced morbidity and accounts for important use of health care resources. There also was a significant association of MDIs with longer treatment delay, which in turn may contribute to worse event-free survival in the affected patients as has been demonstrated by others for osteosarcoma patients [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 72%
“…Conversely, in osteosarcoma, a study from Beirut reviewed 38 pediatric patients <18 years old from 2001–2012 with localized disease [ 50 ]. Patients were given neoadjuvant chemotherapy with the goal of getting patients to definitive local control with surgical resection at week 10.…”
Section: Resultsmentioning
confidence: 99%